LEGAL PROTECTION FOR PHOTOGRAPHERS REGARDING PORTRAITS USED IN TRADEMARKS - Widiya Fitrianda; Sunarmi; Saidin; T. Keizerina Devi A. (Jurnal Hukum Samudra Keadilan, 2024)
Copyright and trademarks are aspects of intellectual property rights (IPR) with different protection concepts and objectives. Copyright aims to protect creations in the fields of art, literature, and science, whereas trademarks aim to protect distinguishing signs of goods and/or services marketed. This research aims to identify, examine, and analyse legal protection for photographers concerning portraits used in trademarks. This study employs normative legal research methods using statutory and case law approaches. The results indicate that legal protection for photographers is regulated in Article 1, Points 1 and 10, Articles 5, and 9 of Law No. 28 of 2014, and Article 21, paragraph (2), letter a of Law No. 20 of 2016. This protection encompasses moral rights and economic rights, which are granted automatically once the creation is expressed in a tangible form that can be seen, read, or heard. Thus, a portrait included in a trademark never loses its exclusive right as copyrighted material. Commercial use by other parties must be based on permission from the creator or copyright holder.